Valorization of buffalo mozzarella cheese whey as human functional food and soil fertilizer - Raffaele Conte; Anna Valentino; Silvia Romano; Sorur Yazdanpanah; Anna Di Salle; Fahd Kandsi; Gianfranco Peluso (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This study examines the potential of transforming buffalo mozzarella cheese whey, a significant byproduct in Mediterranean and Middle Eastern dairy production, into valuable resources. The focus is on utilizing whey as both a functional food for human consumption and a soil fertilizer, addressing waste management issues and promoting economic and environmental sustainability.